2014
DOI: 10.1002/lt.23957
|View full text |Cite
|
Sign up to set email alerts
|

Reframing the impact of combined heart-liver allocation on liver transplant wait-list candidates

Abstract: Simultaneous heart-liver transplantation, although rare, has become more common in the U.S. When the primary organ is a heart or liver, patients receiving an offer for the primary organ automatically receive the second, non-primary organ from that donor. This policy raises issues of equity—i.e. whether liver transplant-alone candidates bypassed by heart-liver recipients are disadvantaged. No prior published analyses have addressed this issue, and few methods have been developed as a means to measure the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…4,17 Waitlist removal was modeled as a binary outcome given the short time interval from initial organ offer to waitlist removal date (median 10 days; 72.9% of removals for death or clinical deterioration occurring within 30 days of an organ offer being declined, and 81.5% within 60 days) between being ranked first and subsequent outcomes of death or transplantation (the outcome in >95% patients ranked first). 17,18 Lastly, we evaluated the graft-specific outcome of graft failure (recipient death or retransplantation 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…4,17 Waitlist removal was modeled as a binary outcome given the short time interval from initial organ offer to waitlist removal date (median 10 days; 72.9% of removals for death or clinical deterioration occurring within 30 days of an organ offer being declined, and 81.5% within 60 days) between being ranked first and subsequent outcomes of death or transplantation (the outcome in >95% patients ranked first). 17,18 Lastly, we evaluated the graft-specific outcome of graft failure (recipient death or retransplantation 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Allograft utilization in particular is a difficult question to objectively address in this small population. However, in heart-liver transplantation, Goldberg et al 28 found that although transplant is delayed for liver transplant waitlist candidates bypassed by heart-liver recipients, they do not have excess mortality compared with 3 sets of matched controls. While bypassing liver-alone patients might not affect their survival, remaining on the waitlist is significantly detrimental to survival for LLT patients compared with either liver- or lung-only waitlist patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, one may argue that isolated transplant candidates could be disadvantaged by prioritization of combined organ transplant candidates. However, based on the OPTN data of 2007–2013, Goldberg concluded that single‐organ candidates — who were bypassed on the waiting list by cLiThTx candidates — did not experience an increased waitlist mortality compared with matched controls .…”
Section: Discussionmentioning
confidence: 99%